2007
DOI: 10.1139/z07-091
|View full text |Cite
|
Sign up to set email alerts
|

Serendipitous discovery of a novel protostrongylid (Nematoda: Metastrongyloidea) in caribou, muskoxen, and moose from high latitudes of North America based on DNA sequence comparisons

Abstract: Fecal samples are often the only feasible means to assess diversity of parasites in wildlife; however, definitive identification of egg or larval stages in feces by morphology is rarely possible. We determined partial sequences from the second internal transcribed spacer region (ITS-2) of nuclear ribosomal DNA for first-stage, dorsal-spined larvae (DSL) in feces from caribou ( Rangifer tarandus tarandus (L., 1758), Rangifer tarandus caribou (Gmelin, 1788), Rangifer tarandus grantii (Allen, 1902)), muskoxen ( O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
100
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(109 citation statements)
references
References 34 publications
5
100
1
Order By: Relevance
“…Larvae of Parelaphostrongylus odocoilei, a muscle worm, have been identified in this population of boreal caribou (Jenkins et al, 2005). In addition, P. odocoilei has been isolated from boreal caribou in several locations in Alberta, and P. andersoni has been found in barrenground caribou in the Northwest Territories and in caribou in Labrador, suggesting that these parasites are widespread in woodland caribou of central and northcentral Canada (Gray and Samuel, 1986;Lankester and Hauta, 1989;Jenkins et al, 2005;Kutz et al, 2007). Although P. odocoilei is most likely responsible for the protostrongylid larvae seen in these caribou, concurrent or mixed infection cannot be ruled out without further molecular diagnostics.…”
Section: Parasitologymentioning
confidence: 93%
See 3 more Smart Citations
“…Larvae of Parelaphostrongylus odocoilei, a muscle worm, have been identified in this population of boreal caribou (Jenkins et al, 2005). In addition, P. odocoilei has been isolated from boreal caribou in several locations in Alberta, and P. andersoni has been found in barrenground caribou in the Northwest Territories and in caribou in Labrador, suggesting that these parasites are widespread in woodland caribou of central and northcentral Canada (Gray and Samuel, 1986;Lankester and Hauta, 1989;Jenkins et al, 2005;Kutz et al, 2007). Although P. odocoilei is most likely responsible for the protostrongylid larvae seen in these caribou, concurrent or mixed infection cannot be ruled out without further molecular diagnostics.…”
Section: Parasitologymentioning
confidence: 93%
“…Clinical disease associated with Toxoplasma gondii has not been reported in free-ranging caribou (Kutz et al, 2001); however, experimental infection of reindeer caused acute, severe, and fatal hemorrhagic enteritis (Oksanen et al, 1996), and fatal transplacental toxoplasmosis has been reported in a naturally infected reindeer (Dubey et al, 2002). Toxoplasma gondii poses a potential public health risk for humans handling or consuming raw meat from infected animals, and further study of definitive hosts for this parasite in northern ecosystems, as well as the host range, distribution, and intensity of infection in boreal caribou, is needed.…”
Section: Parasitologymentioning
confidence: 98%
See 2 more Smart Citations
“…For example, the technique popularly known as genetic or DNA barcoding offers the possibility of performing nondestructive monitoring of hosts for parasites. This creates the potential to shift from logistically challenging field collections, necropsy, and morphological characterization based on assessments of a few hosts to more geographically extensive, siteintensive, and near-simultaneous sampling across ecosystems, thus linking landscape to regional scales for assemblages of host species and populations (e.g., Jenkins et al, 2005;Kutz et al, 2007). This means we now have or can develop the capacity to more readily assess parasite impacts on host species that are rare or endangered.…”
Section: Monitormentioning
confidence: 99%